Assessment of wall stresses and mechanical heart power in the left ventricle: Finite element modeling versus Laplace analysis - Gsell, Matthias A. F. (Int J Numer Method Biomed Eng, 2018)
INTRODUCTION: Stenotic aortic valve disease (AS) causes pressure overload of the left ventricle (LV) that may trigger adverse remodeling and precipitate progression towards heart failure (HF). As myocardial energetics can be impaired during AS, LV wall stresses and biomechanical power provide a complementary view of LV performance that may aide in better assessing the state of disease. OBJECTIVES: Using a high‐resolution electro‐mechanical (EM) in silico model of the LV as a reference, we evaluated clinically feasible Laplace‐based methods for assessing global LV wall stresses and biomechanical power. METHODS: We used N = 4 in silico finite element (FE) EM models of LV and aorta of patients suffering from AS. All models were personalized with clinical data under pretreatment conditions. Left ventricle wall stresses and biomechanical power were computed accurately from FE kinematic data and compared with Laplace‐based estimation methods, which were applied to the same FE model data. RESULTS AND CONCLUSION: Laplace estimates of LV wall stress are able to provide a rough approximation of global mean stress in the circumferential‐longitudinal plane of the LV. However, according to FE results, spatial heterogeneity of stresses in the LV wall is significant, leading to major discrepancies between local stresses and global mean stress. Assessment of mechanical power with Laplace methods is feasible, but these are inferior in accuracy compared with FE models. The accurate assessment of stress and power density distribution in the LV wall is only feasible based on patient‐specific FE modeling.